2010
DOI: 10.1371/journal.pone.0011044
|View full text |Cite
|
Sign up to set email alerts
|

Airway Microbiota and Pathogen Abundance in Age-Stratified Cystic Fibrosis Patients

Abstract: Bacterial communities in the airways of cystic fibrosis (CF) patients are, as in other ecological niches, influenced by autogenic and allogenic factors. However, our understanding of microbial colonization in younger versus older CF airways and the association with pulmonary function is rudimentary at best. Using a phylogenetic microarray, we examine the airway microbiota in age stratified CF patients ranging from neonates (9 months) to adults (72 years). From a cohort of clinically stable patients, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
411
8
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(460 citation statements)
references
References 71 publications
35
411
8
6
Order By: Relevance
“…In contrast, several cross-sectional and longitudinal studies of adults have shown that diversity decreases with age and declining lung function (14,18,22,23). Analyses of respiratory specimens from persons with end-stage lung disease or from lung explants show very constrained communities, often limited to a single dominant species (23,27).…”
Section: The Lung Microbiome In Cfmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, several cross-sectional and longitudinal studies of adults have shown that diversity decreases with age and declining lung function (14,18,22,23). Analyses of respiratory specimens from persons with end-stage lung disease or from lung explants show very constrained communities, often limited to a single dominant species (23,27).…”
Section: The Lung Microbiome In Cfmentioning
confidence: 97%
“…The Human Microbiome Project, a National Institutes of Health-sponsored initiative launched in 2007, applying culture-independent methods to assess bacterial ecology, has significantly broadened this view. Numerous studies now provide compelling evidence that the airways of persons with CF may be inhabited by diverse bacterial communities composed of dozens of species (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In addition to "typical" CF pathogens, "nonpathogenic oral bacteria," including many obligate and facultative anaerobic species, are often present in densities that well exceed those of the traditional opportunists associated with CF (4).…”
Section: The Lung Microbiome In Cfmentioning
confidence: 99%
See 1 more Smart Citation
“…Most mortality in CF is due to microbial infections of the lungs, which lead to eventual respiratory failure (Cystic Fibrosis Foundation, 2008). Pseudomonas aeruginosa, Staphylococcus aureus and Burkholderia cepacia are common pathogens cultured from adult CF patients, but recent studies have demonstrated that microbial communities in the CF airways are highly diverse (Armougom et al, 2009;Rogers et al, 2009;Cox et al, 2010;Guss et al, 2011). Culture-based analysis of bronchoalveolar lavage (BAL) and autopsy samples indicates that microbial populations vary significantly in different spatial regions of the CF lung (Smith et al, 1998;Gutierrez et al, 2001;Gilchrist et al, 2011).…”
mentioning
confidence: 99%
“…À côté de P. aeruginosa, d'autres espèces ou genres (Streptococcus, Prevotella, Veillonella, Rothia, Actinomyces, Gemella, Granulicatella, Fusobacterium, Neisseria, Atopobium, etc.) ont été identifiés comme étant importants dans la constitution du microbiote pulmonaire au cours de la mucoviscidose [9,11,[13][14][15][16][17][18][19][20]. L'ensemble de ces études tend à montrer qu'il existe une corrélation significative entre la diversité du microbiome pulmonaire et l'âge, le statut clinique et l'état de la fonction pulmonaire des patients [11, 15-17, 20, 26].…”
Section: Microbiome Pulmonaire Et Mucoviscidoseunclassified